Risk management and profitability of commercial banks of Western Balkans countries of Kosovo, Albania, North Macedonia, and Serbia - Alshiqi, Sevdie; Sahiti, Arbana (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
Due to their importance, commercial banks currently play a very important role in national financial systems. The profitability of commercial banks depends on how they manage their loans, and credit risk management is thus crucial in the banking system, risk management is significant activity of commercial bank. The main purpose of this study is to observe the extent to which bank profitability is dependent on credit risk management, with a focus on commercial banks in the Western Balkans (Kosovo, Albania, North Macedonia and Serbia). The results reveal a certain assured correlation among credit risk as well as the profitability of banks, where the ratio of non-performing loans (NLPR) has a positive effect on return on equity (ROE) and return on assets (ROA). Capital Insufficiency (CAR) shows that positive dependence is without any statistical significance on return on equity (ROE) and return on assets (ROA).